The Neuro-axitis in your choreoathetoid form - Gonzáles Olaechea, Maximiliano (1922)
Lesson in the Medical Clinic of the Hospital "Dos de Mayo" Neuro-axitis in your choreoathetoid form by Professor Dr. Maximiliano Gonzales Olaechea, Professor of Clinical Medicine, National Academy of Medicine of Lima.